Two Weeks of Wearing a Knee Brace Compared With Minimal Intervention on Kinesiophobia at 2 and 6 Weeks in People With Patellofemoral Pain: A Randomized Controlled Trial - Priore, Liliam B. [UNESP]; Lack, Simon; Garcia, Carmen [UNESP]; Azevedo, Fabio M. [UNESP]; de Oliveira Silva, Danilo [UNESP] (Elsevier, 2020)
Objective: To investigate the effect of a knee brace compared with minimal intervention on self-reported kinesiophobia and function, objective function, and physical activity level in people with patellofemoral pain (PFP). Design: Single-blind randomized controlled trial (1:1), parallel. Participants: Individuals with PFP (N=50). Main Outcome Measures: Primary: kinesiophobia (Tampa Scale for Kinesiophobia). Secondary: self-reported function (Anterior Knee Pain Scale), physical activity level (International Physical Activity Questionnaire), and objective function (forward step-down test). Outcomes were assessed at baseline (T0), at the end of the intervention (2wk) (T1), and at 6 weeks after baseline (T2). Intervention: Participants were randomly assigned to 1 of 2 interventions groups: (1) use of knee brace for 2 weeks during daily living, sports, or painful tasks (brace group) and (2) educational leaflet with information about PFP (leaflet group). Results: The knee brace reduced kinesiophobia in people with PFP compared with minimal intervention with moderate effect size at T1=mean difference (95% CI) −5.56 (−9.18 to −1.93) and T2=−5.24 (−8.58 to −1.89). There was no significant difference in self-reported and objective function and physical activity level. Conclusions: The knee brace improved kinesiophobia immediately after intervention (at 2wk) and at 6-week follow-up in people with PFP compared with minimal intervention. A knee brace may be considered within clinically reasoned paradigms to facilitate exercise therapy interventions for people with PFP.
Keywords: Fear; Knee; Orthotic devices; Patellofemoral pain syndrome; Rehabilitation